Comparison of Dexmedetomidine Infusion with Saline Placebo for Smooth Extubation in Hypertensive Patient for Major Surgery - Franklin, Sheeba (International Journal of Innovative Research in Medical Science, 2017)
Background: The objective of this study was to compare the effects of intravenous dexmedetomidine and saline placebo on recovery characteristics in hypertensive patients. Methods: In a double blinded trial, forty patients detected to have hypertension were randomly allocated to receive either dexmedetomidine 0.5 μg /kg/h (Group D) (n = 20) or saline placebo (Group N) (n = 20) intravenously. Level of sedation and coughing was evaluated using observer assessment sedation score (OSSA). The time for tracheal extubation and emergence from anaesthesia were recorded. Results: The degree of sedation and airway reflexes and circulatory responses at suction and extubation were analyzed and was found to be better in Group D (P=0.013). Smoothness of extubation assessed as coughing on endotracheal tube was comparable in both the groups (P=0.527). There was highly statistically significant increase in time for tracheal extubation and emergence from anaesthesia in group D (P<0.001). Conclusion: These findings suggest that an infusion of dexmedetomidine in hypertensive patients attenuates airway reflexes during surgery and at extubation, thus provided stable safe and reliable extubation.